Carboxylic acid functionalized sesame straw: A sustainable cost-effective bioadsorbent with superior dye adsorption capacity. (August 2017) - Feng, Yanfang; Liu, Yang; Xue, Lihong; Sun, Haijun; Guo, Zhi; Zhang, Yingying; Yang, Linzhang
Graphical abstract: Highlights: Carboxylic acids functionalized bioadsorbents was prepared for cationic dye removal. Citric acid and tartaric acid functionalized sesame straw (SSCA and SSTA) were prepared. SSCA exhibited an adsorption capacity of 650 mg g −1 for MB, higher than some activated carbon. Cost evaluation analysis showed SSCA was the most cost-effect bioadsorbent in the present study. SSCA met "4-E" criteria: Efficient, Economical, Environmental-friendly, and Easily-produced. Abstract: This study prepared a carboxylic functionalized bioadsorbent that met the "4-E" criteria: Efficient, Economical, Environmentally friendly, and Easily-produced. Sesame straw ( Sesamum indicum L.) was functionalized through treatment with citric acid (SSCA) and tartaric acid (SSTA). The products were examined for adsorption capacity and mechanisms. Langmuir model gave the best fit for the isotherm data, and the maximum monolayer adsorption capacity of SSCA was 650 mg g −1 for methylene blue (MB). The excellent dye adsorption capacity of SSCA can be attributed to the introduction of ester groups during citric-acid modification and the tube-like structures (i.e., sesame straw cell wall remnants). At last, the cost of carboxylic acid functionalized bioadsorbents was evaluated, which showed that SSCA would be the most cost-effective bioadsorbent. Additionally, this study presents a thermo-decomposition methodology for contaminant-loaded bioadsorbent. Results showed that SSCA is probably one of the few bioadsorbents that can be produced and applied in industrial scale.